PRESSURE OSCILLATIONS IN TRANSIENT PROCESSES OF HYDRAULIC SYSTEMS WITH VARIABLE DISPLACEMENT PUMPS - Zaionchkovskyi, Hennadii; Butko, Volodymur; Tarasenko, Taras (Proceedings of National Aviation University (archive), 2016)
In aviation hydraulic drive of high power as a power supply the axial-piston variable displacement pumps became wide spreaded. The pump operational modes with air isolation and cavitation are accompanied by increased noise, delivery reduction and intensive pressure oscillations. The negative results of such phenomena are hydraulic elements erosion, pipeline fatigue failure, working fluid viscosity reduction and its contamination by wear products. The mechanism of cavitation rising in axial-piston pumps is considered, and factors which influence the cavitation rising and working fluid aeration are specified. The features of transient processes in aircraft hydraulic systems with variable displacement pumps are considered. It has been showed that as the pump delivery changes from its minimum to maximum great pressure oscillations in the aircraft pressure pipeline of the hydraulic system takes place, and have a negative influence on the pump service life. The recommendations concerning such pressure oscillation reduction are given.